Deoxygenative α-alkylation and α-arylation of 1, 2-dicarbonyls. Issue 34 (6th July 2020) - Jin, Shengfei; Dang, Hang T.; Haug, Graham C.; Nguyen, Viet D.; Arman, Hadi D.; Larionov, Oleg V.
Abstract : α-Branched carboxylic acids and other carbonyls are readily accessed by a metal- and base-free deoxygenative α-alkylation and α-arylation of 1, 2-dicarbonyls via boron enolates, resulting in a tricomponent coupling with unconventional electrophiles. Abstract : Construction of C–C bonds at the α-carbon is a challenging but synthetically indispensable approach to α-branched carbonyl motifs that are widely represented among drugs, natural products, and synthetic intermediates. Here, we describe a simple approach to generation of boron enolates in the absence of strong bases that allows for introduction of both α-alkyl and α-aryl groups in a reaction of readily accessible 1, 2-dicarbonyls and organoboranes. Obviation of unselective, strongly basic and nucleophilic reagents permits carrying out the reaction in the presence of electrophiles that intercept the intermediate boron enolates, resulting in two new α-C–C bonds in a tricomponent process.